Understanding digital public relations practices among exemplar school principals in Malaysian schools - Saraih, Emelia Fantoza; Wong, Su Luan; Asimiran, Soaib; Md Khambari, Mas Nida (Universiti Putra Malaysia, 2021)
In recent years, Digital Leadership (DL) has been recognised as an important practice for school principals. DL focuses on Information and Communication Technology (ICT) in support of school principals’ leadership practice. This qualitative study was undertaken with the aim of understanding DL among principals from four High Performing Schools (HPS) in Malaysia, particularly from the perspective of public relations. Semi-structured interviews were employed involving four exemplar school principals as the main respondents and 12 school staff as the secondary respondents of the study. The findings indicate that social media has become the contemporary public relations conduit among exemplar Malaysian school principals. The findings also suggest that third parties, such as students, parents, and alumni, enhance school principals’ public relations practices via their social media accounts. The aforesaid findings have meaningful implications for other school principals in similar school settings and contexts to better integrate social media in their public relations practice, especially by leveraging third-party social media accounts.